Cerebrospinal Fluid B-lymphocyte Chemoattractant CXCL13 in the Diagnosis of Acute Lyme Neuroborreliosis in Children. Issue 12 (December 2017) - Barstad, Bjørn; Tveitnes, Dag; Noraas, Sølvi; Selvik Ask, Ingvild; Saeed, Maryam; Bosse, Franziskus; Vigemyr, Grete; Huber, Ilka; Øymar, Knut
Abstract : Background: Current markers of Lyme neuroborreliosis (LNB) in children have insufficient sensitivity in the early stage of disease. The B-lymphocyte chemoattractant CXCL13 in the cerebrospinal fluid (CSF) may be useful in diagnosing LNB, but its specificity has not been evaluated in studies including children with clinically relevant differential diagnoses. The aim of this study was to elucidate the diagnostic value of CSF CXCL13 in children with symptoms suggestive of LNB. Methods: Children with symptoms suggestive of LNB were included prospectively into predefined groups with a high or low likelihood of LNB based on CSF pleocytosis and the detection of Borrelia antibodies or other causative agents. CSF CXCL13 levels were compared between the groups, and receiver-operating characteristic analyses were performed to indicate optimal cutoff levels to discriminate LNB from non-LNB conditions. Results: Two hundred and ten children were included. Children with confirmed LNB (n=59) and probable LNB (n=18) had higher CSF CXCL13 levels than children with possible LNB (n=7), possible peripheral LNB (n=7), non-Lyme aseptic meningitis (n=12), non-meningitis (n=91) and negative controls (n=16). Using 18 pg/mL as a cutoff level, both the sensitivity and specificity of CSF CXCL13 for LNB (confirmed and probable) were 97%. Comparing only children with LNB and non-Lyme aseptic meningitis, the sensitivity and specificity with the same cutoff level were 97% and 83%, respectively. Conclusion: CSF CXCL13 is a sensitive marker of LNB in children. The specificity to discriminate LNB from non-Lyme aseptic meningitis may be more moderate, suggesting that CSF CXCL13 should be used together with other variables in diagnosing LNB in children.